Why we should improve current practice of diagnosing and treating pulmonary large cell neuroendocrine carcinomas in patients with advanced disease. Issue 4 (26th October 2017) - Derks, Jules; van Suylen, Robert Jan; Thunnissen, Erik; den Bakker, Michael; Groen, Harry; Smit, Egbert; Damhuis, Ronald; van den Broek, Esther; Speel, Ernst-Jan; Dingemans, Anne-Marie C.
In response to our manuscript on first-line chemotherapy treatment for metastatic pulmonary large cell neuroendocrine carcinoma (LCNEC) [1], Rossi and co-workers raised their concerns about the validity of our results by questioning the accuracy of LCNEC diagnosis on a biopsy specimen. We would like to thank the authors for their critical appraisal, underscoring the need to increase awareness among pulmonologists, oncologists and pathologists of the diagnostic issues and consequences of metastatic LCNEC diagnosed on a biopsy specimen. Current criteria for LCNEC diagnosed on a biopsy specimen are in need of improvement http://ow.ly/lRP730fu552